Isothermal structure development in submicron P3HT layers studied by fast scanning chip calorimetry. (28th January 2015) - Van den Brande, N.; Van Assche, G.; Van Mele, B.
Abstract: Using the advanced thermal analysis technique of fast scanning chip calorimetry, an isothermal crystallization study was undertaken on poly(3-hexyl thiophene) (P3HT), a workhorse material for organic photovoltaics (OPVs). As a model system, poly(butylene terephthalate) (PBT), a polyester with similar transition temperatures was first analyzed. By using gold foil as a substrate, it was possible to perform this study on thin layers, making the results more applicable for actual OPVs, where thin layers are used for charge generation. Using heating and cooling rates of 30 000 K s −1, all non-isothermal processes could be avoided, and the evolution of isothermally formed crystals could be analyzed. The bell-shaped curve of crystallization rate as a function of isothermal crystallization temperature was constructed for a ca. 550 nm thin P3HT layer. Graphical abstract: Highlights: Isothermal crystallization kinetics were studied using fast scanning chip calorimetry. A methodology to perform these measurements on sub-micron layers was developed. PBT was chosen as a test system, with success. The method was applied to P3HT. The bell-shaped crystallization rate curve was constructed between 360 K and 450 K.